Determinación de la calidad del aire producto de la combustión del parque automotor a diesel en base a la modelación de datos obtenidos en investigaciones con el opacímetro en la ciudad de Latacunga. - Ramírez Flores, Oscar Absalón (2021)
The air we currently breathe has been modified, given by the progressive increase in the product of the hydrocarbon combustion automobile fleet, daily pollutants are emitted as carbon dioxide (CO2), carbon monoxide (CO), sulfur dioxide. (SO2); also, dust and particles generated by internal combustion engines, as a constructive activity. The concentration of the aforementioned pollutants in the local area reaches a very high level, especially in the center of the city of Latacunga, where vehicle traffic is very dense, which affects the health of residents and the different components of the urban ecosystem. , microclimate and climate and hydrology. The National Institute of Statistics and Census (IEC) estimates that; In the province of Cotopaxi, 54,356 vehicles were registered during 2015, of which 26,653 are diesel engines. These vehicles generate opacity from their leaks and cause a great environmental impact on the air of the city. To determine their environmental quality, a database obtained from previous investigations of two urban parishes San Buenaventura and Ignacio Flores was used where the SPSS software to make the respective modeling and correlations of the variables, thus obtaining that of a total of 252 vehicles analyzed, 47.2% (119) comply with the opacity parameters established in the NTE INEN 2207: 2002 standard, while the 52.8% (133) do not comply, indicating that the air quality in the Latacunga canton is at risk due to the medium increase in the number of vehicles since a significant percentage of sampled diesel vehicles exceed the maximum permitted opacity limits. Once the data obtained from the three types of regression had been analyzed, it was determined that the data better fit the cubic nonlinear regression, due to the fact that they present an R2 of 0.609, that is, the vehicle's mileage will influence a 60.9% in their opacity values, there are other factors that affect the opacity emanation of diesel cars, such as changing oil and diesel filters